2006
DOI: 10.1086/504710
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Radio Emission from Type Ia Supernovae

Abstract: We present and discuss the radio observations of 27 Type Ia supernovae (SNe Ia), observed over two decades with the Very Large Array. No SN Ia has been detected so far in the radio, implying a very low density for any possible circumstellar material established by the progenitor, or progenitor system, before explosion. We derive 2 upper limits to a steady mass-loss rate for individual SN systems as low as $3 ; 10 À8 M yr À1, which argues strongly against white dwarf accretion via a stellar wind from a massive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(163 citation statements)
references
References 53 publications
8
155
0
Order By: Relevance
“…Spectropolarimetry of heavily reddened SNe Ia (Patat et al 2015), and the lack of infrared thermal emission (Johansson et al 2013(Johansson et al , 2016) from some of the same events, point to the absence of dust in the CS environments. In addition, strong limits from X-ray (Margutti et al 2014) and radio (Panagia et al 2006;Chomiuk et al 2016) observations point to very low mass-loss rates from the progenitor systems. Nevertheless, there are observations suggesting the existence of outflowing matter from SNe Ia.…”
Section: Introductionmentioning
confidence: 99%
“…Spectropolarimetry of heavily reddened SNe Ia (Patat et al 2015), and the lack of infrared thermal emission (Johansson et al 2013(Johansson et al , 2016) from some of the same events, point to the absence of dust in the CS environments. In addition, strong limits from X-ray (Margutti et al 2014) and radio (Panagia et al 2006;Chomiuk et al 2016) observations point to very low mass-loss rates from the progenitor systems. Nevertheless, there are observations suggesting the existence of outflowing matter from SNe Ia.…”
Section: Introductionmentioning
confidence: 99%
“…Such an assumption is necessary because the correlation between wind density and radio luminosity for SNe Ia cannot be calculated from theory at this point. In the absence of theoretical or observational support for such an assumption the very low mass-loss rates claimed by Panagia et al (2006) cannot yet be considered definitive ). The radio non-detections may therefore still permit the symbiotic scenario.…”
Section: Discussionmentioning
confidence: 98%
“…from the WD to be consistent with our Hα nondetections. For a 1.4 M ⊙ primary and a 1.0 M ⊙ secondary, this corresponds to an orbital period of 20 yr. Panagia et al (2006) rely on the assumption that SN Ia radio light curves behave identically to those of SNe Ib/c. Such an assumption is necessary because the correlation between wind density and radio luminosity for SNe Ia cannot be calculated from theory at this point.…”
Section: Discussionmentioning
confidence: 99%
“…We choose a value of u w = 10 km s −1 , which is typical of the winds of evolved intermediate-mass stars (e.g. Panagia et al 2006).…”
Section: The Gas Bubblementioning
confidence: 99%
“…No direct detection has been made at this point, but upper limits are reaching interesting values. Using the VLA, Panagia et al (2006) found upper limits of ∼10 −6 M yr −1 based on observations of 27 SNe Ia. Their analysis is extrapolated from the assumption that the process behind radio emission from SNe Ia are similar to those of SNe Ib/c.…”
Section: Upper Limitsmentioning
confidence: 99%